2016
DOI: 10.1515/acs-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon source utilization and hydrogen production by isolated anaerobic bacteria

Abstract: Five bacterial isolates were tested for their ability to generate hydrogen during anaerobic fermentation with various carbon sources. One isolate from sheep rumen was identified as Escherichia coli and four isolates belonged to Clostridium spp. Glucose, arabinose, ribose, xylose, lactose and cellobiose were used as carbon sources. Results showed that all bacterial strains could utilize these compounds, although the utilization of pentoses diminished growth yield. The excretion of monocarboxylic acids (acetate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(24 reference statements)
1
3
0
Order By: Relevance
“…In environmental conditions, microorganisms' survival can be predicted by the capability to utilise a range of available carbohydrates as carbon and energy sources [65]. The efficient uptake rate of glucose agrees with the results of Jame et al, which showed that all investigated bacterial isolates utilised this monosaccharide as a carbon source [66]. Due to the fact that glucose is the preferable sugar, most presumably because it can enter glycolysis directly, whereas other sugars need to be enzymatically transformed.…”
Section: Discussionsupporting
confidence: 85%
“…In environmental conditions, microorganisms' survival can be predicted by the capability to utilise a range of available carbohydrates as carbon and energy sources [65]. The efficient uptake rate of glucose agrees with the results of Jame et al, which showed that all investigated bacterial isolates utilised this monosaccharide as a carbon source [66]. Due to the fact that glucose is the preferable sugar, most presumably because it can enter glycolysis directly, whereas other sugars need to be enzymatically transformed.…”
Section: Discussionsupporting
confidence: 85%
“…spores was studied, since previous works found Clostridium perfringens sp. to be the most dominant hydrogen producing culture [23][24][25][26][27]. The concentration was observed to vary by a factor of up to 12, ranging from a maximum of 150 CFU/mg found for the activated sludge sample (IN1) to a minimum of 13 CFU/mg (IN2).…”
Section: Analytical Characterization Of Fw and Inoculamentioning
confidence: 98%
“…Several works found Clostridium perfringens sp. to be the most dominant hydrogen producing culture [23][24][25][26][27], and it is widely adopted when evaluating hydrogen production from a pure culture [24,28]. Spores were measured because Clostridium sp.…”
Section: Analytical Parametersmentioning
confidence: 99%
See 1 more Smart Citation